Service orchestration over clouds and networks. (2018) - Muhammad, Afaq; Kang, Dong-hun; Seok, Seung-Joon; Song, Wang-Cheol
The dynamic and constantly changing nature of request by a typical end-user for resource allocation demands service orchestration over clouds and networks. In order to meet such requests, it is necessary to control and aggregate diverse types of resources from cloud infrastructures and network functions. To that end, in this paper, we propose an orchestration framework for resource management and provisioning. The proposed orchestrator manages and provisions resources by: 1) exploiting application program interfaces (APIs) provided by the cloud provider in order to control/manage/allocate storage and compute resources; 2) interacting with software-defined networking (SDN) controller to get the details of the available resources, and instructing the changes/rules to manage the network based on the cloud service requirements. For resource allocation, an algorithm is proposed, which allocates resources on the basis of unutilised resources in a pool of virtual machines. An algorithm has been taken into account for comparison with the proposed resource allocation algorithm. The experiment results show that the considered algorithm is outperformed by the proposed algorithm.